Description Of Mother Knowledge About Care Infant Baby - Sri Eka Juniarli; Risnawati (Jurnal Life Birth, 2017)
Jaundice is yellowing of the sclera, skin or other tissue due to accumulation of bilirubin in the body or accumulation of bilirubin in the blood more than 5 mg / dl in 24 hours, which indicates the occurrence of functional disorders of the liver, biliary system, or hematological system. The general objective of this research is to find out the description of midwife knowledge about care for jaundice at Gattareng Health Center, Gantarang District, Bulukumba Regency in 2016. The research design is a model or method used by researchers to conduct a study that gives direction to the course of research. This type of research uses descriptive design. In this study using a sampling technique by means of total sampling or saturated sampling. The population and sample in this study were 32 mothers who gave birth at the Gattareng Health Center, Gantarang District, Bulukumba Regency in 2016. The research was conducted at the Gattareng Health Center, Gantarang District, Bulukumba Regency, which began on June 16 until May 24, 2016. The distribution of research found that 32 respondents, who have knowledge of jaundice baby care with good categories are as many as 2 mothers (6.3%) with enough categories as many as 2 mothers (6.3%), and in the category of less than 28 mothers (87.5%). It can be concluded that the lack of knowledge possessed by mothers about jaundice baby care at the Gattareng Health Center, Gantarang District, Bulukumba Regency in 2016 because most mothers only had low and middle education. And most of the mothers do not have jobs and the lack of information obtained by mothers from health workers (midwives).